2008
DOI: 10.1007/s11250-007-9124-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ketosis and dairy cows’ blood metabolites in intensive production farms of the periurban area of Dakar

Abstract: This study which involved 140 Holstein and Montbeliard was carried out in the periurban area of Dakar with the aim to establish the relationship between ketosis, milk production and biochemical blood metabolites. The results showed that ketosis is a real problem in periurban farms around the city of Dakar with high proportions of 33.57% for subclinical ketosis and 6.43% for clinical ketosis. In their second month of milking, cows with subclinical ketosis had a decrease of 12.4 and 15.,6% in milk yield respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
5
20
0
3
Order By: Relevance
“…This finding indicates that careful examination of Ketotic buffalo were hypoglycemic with high level of serum BHB. Similar findings were reported previously in buffalo (Sharma and Rakesh 2001;Ghanem and El-deeb 2010) and cows (Akamatsu et al 2007;Nazifi et al 2008;Yameogo et al 2008). The decrease of glucose level may occur in response to intake of low energy diet (Bremmer et al 2000), specially at the early stage of lactation when high rate of glucose utilization in the mammary gland is required (Nazifi et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding indicates that careful examination of Ketotic buffalo were hypoglycemic with high level of serum BHB. Similar findings were reported previously in buffalo (Sharma and Rakesh 2001;Ghanem and El-deeb 2010) and cows (Akamatsu et al 2007;Nazifi et al 2008;Yameogo et al 2008). The decrease of glucose level may occur in response to intake of low energy diet (Bremmer et al 2000), specially at the early stage of lactation when high rate of glucose utilization in the mammary gland is required (Nazifi et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Increase of calcium level in ketosis has been reported and could be attributed to primary hyperparathyroidism, increase hepatic vitamin D release, and decrease renal excretion of calcium (Stockham and Scott 2002). However, other reports confirmed presence of hypocalcemia in cows with clinical and subclinical ketosis (Radostits et al 2007;Yameogo et al 2008). In the present study, although there were no significant changes in the calcium level, presence of low phosphorus and magnesium level indicate a state of mineral deficit in buffalo with ketosis.…”
Section: Discussionmentioning
confidence: 87%
“…Azab and Abdel-Maksoud (7) also observed that plasma Ca levels in Baladi does markedly decreased during late pregnancy, reached minimum levels at parturition, and then continued to decrease for 3 weeks postpartum, ultimately returning to the level before pregnancy. Yameogo et al (27) also reported lower average blood calcium concentrations in cows with clinical or subclinical ketosis. This was likely the result of mineral deficiencies that typically result from ketosis due to disturbances in feed consumption, as reported by other researchers (27,29).…”
Section: Discussionmentioning
confidence: 93%
“…Yameogo et al (27) also reported lower average blood calcium concentrations in cows with clinical or subclinical ketosis. This was likely the result of mineral deficiencies that typically result from ketosis due to disturbances in feed consumption, as reported by other researchers (27,29). Furthermore, it has been speculated that ketosis impairs Ca metabolism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation